Word-Based Self-Awareness in Digital Identity : An Existential-Perennial Synthesis Model to Indonesian Christian Education Transformation - Setiyaningtiyas, Nerita; Apriyanto, Dicky; Sugiyana, Sugiyana (LPPM Universitas Pendidikan Mandalika, 2025)
This study examines an educational model based on existential-perennial synthesis for transforming Indonesian Christian education through systematic integration of Word-based self-awareness in digital identity formation. A mixed-methods approach was employed, combining Structural Equation Modeling (SEM) for quantitative data and thematic analysis for qualitative data. The sample consisted of 178 respondents for SEM analysis and 20 participants for in-depth interviews and focus group discussions. The findings reveal significant relationships between social connectivity, self-expression creativity, and self-awareness, which collectively shape personal identity. This study provides a comprehensive framework for developing holistic Christian character education programs that integrate spiritual, social, and creative dimensions to foster authentic and transformative personal identity through faith-based pedagogical approaches.